Sosialisasi Dan Edukasi Ketahanan Pangan Berkelanjutan Melalui Pendekatan Fenomenologi Sosial Ekonomi Ibu Rumah Tangga Petani di Desa Pondidaha, Konawe, Sulawesi Tenggara - Mursal Junus (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Sustainable food security is a strategic issue in rural development that requires a comprehensive approach based on local communities. This community service activity aims to provide socialization and education on sustainable food security through a socio-economic phenomenological approach focusing on the role of farmer housewives in Pondidaha Village, Konawe Regency. The implementation methods include educational lectures, focused group discussions (FGD), field visits, and hands-on sustainable food management practices involving 20 farmer housewife respondents. The results show that 80% of participants gained adequate understanding of sustainable food security concepts, local food diversification strategies, and active roles in improving family welfare through strengthening socio-economic capacity. The main challenges identified include limited access to resources, dual roles of housewives, and seasonal income instability. The implemented solutions include sustainable agriculture management training, food diversification counseling, and improved market access. This socio-economic phenomenology-based education provides a perspective that the life experiences, cultural values, and habits of farmer housewives are key to the success of food security programs at the community level. This activity contributes to increasing awareness, skills, and community participation in realizing sustainable food security in Pondidaha Village.